Foreword: Special issue on "Effects of the solar wind and interplanetary disturbances on the Earth's atmosphere and climate". (November 2016) - Rozanov, E.; Georgieva, K.; Mironova, I.; Tinsley, B.; Aylward, A.
Abstract: The special issue "Effects of the solar wind and interplanetary disturbances on the Earth's atmosphere and climate" discusses the effects of solar wind and interplanetary disturbances on the Earth's atmosphere and climate. After a brief introduction to the solar wind and its geoeffective agents, the results presented in the special issue are highlighted, which include both statistical studies aimed at the identification of atmosphere and climate response to external solar forcing, and attempts to identify responsible physical mechanisms and include some of them in climate models.